Model Based Control of Amine Sweetening Unit - Al Hammadi, Jasim (2005)
A Master of Science Thesis in Mechatronics Submitted to the School of Engineering by Jasim Al Hammadi, "Model Based Control of Amine Sweetening Unit," June 2005. Chair of Committee Dr. Nabil Abdel Jabbar & Co-Advisor Dr. Mohamed Ameen Al Jarrah. Available are Both Soft and Hard Copies of the Thesis.